Phenotypic and molecular characterization of Candida spp. isolated from intramammary infections in dairy animals by PCR-RFLP - DEVENDER SINGH RANA; PANKAJ KUMAR; PAWAN KUMAR; JASLEEN KAUR; SAURABH J TALUKDAR; RAHUL YADAV; MAHAVIR SINGH; JINU MANOJ; RAJESH CHHABRA (Indian Journal of Animal Sciences)
Mastitis is caused by various microorganisms like bacteria, viruses, mycoplasma, algae and yeasts. Of them, fungal infections contribute to 2–13% of the cases, with Candida as the most common genus, although wide variations in prevalence and species are identified. In the present study, 06.66% (n = 40/600) prevalence was observed in mastitic milk samples of cattle and buffalo on the basis of culture examination on blood agar (BA), sabouraud dextrose agar (SDA) and candida differentiation agar (CDA). On SDA, the isolates produced white to creamy, smooth, pasty and convex colonies. However, different isolates could not be differentiated on the basis of colony characteristic on SDA medium. Chromogenic agar such as candida differential agar was able to differentiate different species of Candida on the basis of production of different coloured colonies. In the VITEK®2 compact system, different isolates were identified with diverse level of identification ranging from excellent to acceptable. Furthermore, all of the isolates were confirmed by amplification of internal transcribed spacer (ITS) region by polymerase chain reaction (PCR). For molecular characterization of Candida spp., the PCR products were digested by restriction enzymes (HaeIII and TaqI) for restriction fragment length polymorphism (RFLP) and various patterns were obtained. Furthermore, in-silico RFLP analysis was done with restriction enzymes HaeIII and TaqI, for different Candida species to obtain accurate fragment sizes. PCR-RFLP proved to be a simple, cost effective and accurate method as compared to the phenotypic based methods which are often difficult and time consuming for rapid and species level differentiation of Candida species involved in mycotic mastitis.